Reputation: 4062
// Collacoq link: https://x80.org/collacoq/qezicaroni.coq
Inductive bin : Type :=
| Zero : bin
| One : bin
| ZeroP : bin -> bin
| OneP : bin -> bin.
Inductive bin_carry : Type :=
| ZeroC : bin_carry
| OneC : bin_carry.
(*returns carry, new_state*)
Fixpoint incr' (x : bin) : bin_carry * bin :=
match x with
| Zero => (ZeroC, One)
| One => (OneC, Zero)
| ZeroP x =>
match incr' x with
| (OneC, x') => (ZeroC, OneP x')
| (ZeroC, x') => (ZeroC, ZeroP x')
end
| OneP x =>
match incr' x with
| (OneC, x') => (OneC, ZeroP x')
| (ZeroC, x') => (ZeroC, OneP x')
end
end.
Definition incr (x : bin): bin :=
match incr' x with
| (ZeroC,x) => x
| (OneC,x) => OneP x
end.
(*index_multiplier * result*)
Fixpoint bin_to_nat' (x : bin): nat * nat :=
match x with
| Zero => (2,0)
| One => (2,1)
| ZeroP x =>
match bin_to_nat' x with
| (multiplier,result) => (multiplier * 2,result)
end
| OneP x =>
match bin_to_nat' x with
| (multiplier,result) => (multiplier * 2,result + multiplier)
end
end.
Definition bin_to_nat (x : bin): nat :=
match bin_to_nat' x with
| (_,r) => r
end.
Example bin_test1: bin_to_nat Zero = 0.
Proof. reflexivity. Qed.
Example bin_test2: bin_to_nat (incr Zero) = 1.
Proof. reflexivity. Qed.
Example bin_test3: bin_to_nat (incr (incr Zero)) = 2.
Proof. reflexivity. Qed.
Example bin_test4: bin_to_nat (incr (incr (incr Zero))) = 3.
Proof. reflexivity. Qed.
Example bin_test5: bin_to_nat (incr (incr (incr (incr Zero)))) = 4.
Proof. reflexivity. Qed.
Theorem binary_commute :
forall (x: bin),
bin_to_nat(incr x) = S (bin_to_nat x).
Proof. induction x.
- reflexivity.
- reflexivity.
- replace (ZeroP x) with x.
+ rewrite -> IHx. reflexivity.
+ induction x.
* Abort.
I am going through the Software Foundations book and am stumped on the above. I looked around on the net and found the solution for a different kind of bin formulation, but I do not think the solution there applies here.
The trouble is that in the third -
bullet bin_to_nat (incr (ZeroP x)) = S (bin_to_nat (ZeroP x)
will not simplify and neither it can be rewritten directly. So after learning about replace I thought that might work, but then I get stuck trying to prove Zero = ZeroP Zero
.
I know the problem states that I am free to change the formulation of bin to make proving its commutativity easier, but my hunch is that I am not going to get far with Coq if I get stuck at the above definition. Though unlike the past few times, I do not think I have the tools to get past this yet.
What am I missing here?
Upvotes: 2
Views: 188
Reputation: 12093
replace (ZeroP x) with x.
cannot succeed: for such an equation to hold x
would need to be an infinite term equal to ZeroP (ZeroP (ZeroP (...)))
. What you may want to prove first is that incr
is extensional semantically. i.e.
Theorem incr_ext : forall (x y : bin),
bin_to_nat x = bin_to_nat y -> bin_to_nat (incr x) = bin_to_nat (incr y).
Upvotes: 3